Uso de productos andinos en la gastronomía típica de la parroquia Zumbahua del cantón Pujilí. - Paredes Macas, María José (2024)
The purpose of this research entitled "Use of Andean Products in the typical gastronomy of the Zumbahua parish, Pujilí Canton" was to determine the use of the main Andean products of the Zumbahua parish in the preparation of typical dishes and meals of the area, so allowing to know if the products are still used in a considerable way, or if the trends of use and consumption have been influenced by external factors. For this purpose, a situational diagnosis was carried out in the Zumbahua parish to collect the necessary information that allowed the registration of Andean products and their use in gastronomy. For this data collection, a survey was applied to 374 inhabitants of the area and interviews were conducted to 9 typical food establishments according to the tourism cadastre of 2023. In addition, it was necessary to visit the communities where typical dishes are sold in order to know their ingredients and preparation which contributed to the elaboration. Among the main results, it was stablished that the main used Andean product is the potato with 20%, as well as broad beans with 18%, and corn with 17%. The 88% of the inhabitants consider that Andean products are still used in the preparation of typical dishes, the most consumed is the guinea pig with potatoes with 30% and yahuarlocro with 11%. It should be noted that half of the population (50%) considers that typical cuisine is very important in the parish. On the other hand, 30% of surveyed citizens said that traditional values are being lost in terms of gastronomy which is of relevant importance for the promotion of gastronomic tourism in the sector. Therefore, it was proposed to prepare a cookbook of typical foods including Andean products.